Question-Answer Dialogical Discourse in English and Its Pragmatic Analysis - Ozoda Mehmonova (Indonesian Journal Publisher, 2025)
This article investigates the pragmatic and structural characteristics of question–answer dialogue in English across literary, conversational, and media contexts. Utilizing discourse analysis and pragmatic interpretation of selected English dialogues, the study focuses on ellipsis, intention, and speaker dynamics within dialogue construction. The analysis reveals that question–answer structures are not only tools for information exchange but also serve expressive, strategic, and interpersonal functions. Pragmatic elements such as sarcasm, irony, and implicit meaning are commonly embedded through ellipsis and minimal responses. The study concludes that understanding these features enhances effective communication and provides insight into contextual language use.